Phylogeographic history of Parthenocissus (Vitaceae) in North America based on chloroplast and nuclear DNA sequences - Wu, Di; Meng, Ying; Wen, Jun; Nie, Ze-Long (Frontiers in Plant Science, 2025)
Knowledge of historical distribution and postglacial phylogeographic evolution of plants is important for better understanding their current distribution, population structure and potential fate in the future. Surprisingly, little is known about the post-glacial recolonization history of lianas that are widely distributed in the deciduous or mixed deciduous-evergreen forests in North America. Here, we conducted a phylogeographic study on 47 populations with 398 individuals from the North American Parthenocissus using both chloroplast and nuclear DNA sequences data. A high level of genetic diversity is observed among Parthenocissus populations in North America, with 66.45% of cpDNA and 92.78% of nrDNA genetic variation present within populations. The North American Parthenocissus is roughly grouped into three main lineages with a south to north trend of decline in genetic diversity, which may have been isolated and diverged due to climatic and geographic environmental influences since the late Miocene. Our results indicate that a wide range of gene flow and frequent hybridization are occurring among the Parthenocissus populations and the Edwards Plateau, the southern Appalachian Mountains and the Atlantic coastal plains are their possible glacial refugia in eastern and southern North America. The results for Parthenocissus represent the first phylogeographic analysis of a major lineage of temperate woodland climbers in North America and support the importance of long-distance dispersal events leading to extensive hybridization and gene flow during the post-glacial migration of this plant lineage.